Isolating downward displacement: The solutions and challenges of amino acid racemisation in shell midden archaeology. (5th January 2017) - Koppel, Brent; Szabó, Katherine; Moore, Mark W.; Morwood, Michael J.
Abstract: Shell middens are particularly susceptible to post-depositional processes that can rework and redistribute material through a deposit. As archaeological material is moved from its original primary context, the assumption that a temporal connection exists with spatially associated material becomes tenuous. It therefore becomes critical to identify displaced archaeological material within a deposit to ensure correct chronologies are being built. Radiometric dating techniques can identify individual displaced materials, but are sometimes prohibitively costly to utilise on a large scale. This study presents a new application of amino acid racemisation (AAR) dating that identifies stratigraphically displaced midden shell from within a deposit from the northwest Kimberley, Western Australia. Low-cost AAR analysis of 72 samples identified a sample of downwardly-displaced midden shell. Upon close inspection, comparison of AAR and AMS radiocarbon determinations identified fine-grained inconsistencies. Possible processes generating these discrepancies are considered with future avenues for research presented. While an enormous amount of potential is contained within AAR, more work is required to bring the method to the same level of precision as other commonly utilised dating techniques in archaeological research.